ChemInform Abstract: Catalytic Oxidation of Alcohols to Carbonyl Compounds over Hydrotalcite and Hydrotalcite‐Supported Catalysts. Issue 39 (September 2015) - Mobley, J. K.; Crocker, M.
Abstract Review: 76 refs.